A Survey Study Of Students’ Strategies In Learning Listening Skills During The Covid 19 Pandemic At Uinfas Bengkulu - Nurmala Septiani; Syamsul Rizal; Zelvia Liska Afriani (Yayasan Darussalam Bengkulu, 2022)
The aims of this study was to find out student learning strategies in learning listening skills and how these strategies can help them during the COVID-19 pandemic at UINFAS Bengkulu. This study uses a quantitative descriptive method, data was collected using a questionnaire distributed through Google Forms and interviews. The population in this study was 179 students with 65 students used as research samples for the questionnaire and 5 people for interview data. In this study, the researchers found 1. The dominant metacognitive strategy used by students was compared to the other five strategies. The proportion of memory strategies used by students is: 38.46 %. On cognitive strategy: 36.92%. On compensation strategy: 30.76%. Metacognitive strategy showed: 73, 84%. On the affective strategy: 27.69%. And on social strategy: 32.30%. Based on the results. The metacognitive strategy got the